Bovine serum albumin fibrous biofilm template synthesis of metallic nanomeshes for surface-enhanced Raman scattering and electrocatalytic detection. (July 2020) - Wu, Xiaochen; Lv, Lili; Han, Xiangsheng; Li, Chaoxu
Abstract: Porous metallic architectures with well-defined networks possess multiple reactivity center and large specific surface area, offer improved catalytic activity, adsorption capacity, and sensing abilities than bulk materials, thus be an increasingly popular materials in various fields. However, it is challenging to synthesis porous metallic structures in a green, facile and scalable way. Using bovine serum albumin (BSA) nanofibrous biofilms as sacrificial templates, a variety of porous metallic nanomeshes were readily formed through the adsorption of ions following by air calcination. The microstructures of the metallic nanomeshes are controllable, with pores ranging from 10 −2 to 10 0 μm and particle diameter of 30–270 nm. Specifically, the Au nanomeshes displayed not only high plasmonic resonance properties as SERS substrates, but also multiple reactivity centers as electrochemical sensor for dopamineand H2 O2 . Graphical abstract: Unlabelled Image Highlights: Metallic nanomeshes were template synthesized by bovine serum albumin fibrous biofilms. Au nanomeshes offered high plasmonic resonance properties as SERS substrates. Au nanomeshes offered multiple reactivity centers as sensitive electrosensor.